Associations between Extracurricular Activity and Self-Regulation: A Longitudinal Study from 5 to 10 Years of Age. Issue 1 (September 2015) - Piché, Geneviève; Fitzpatrick, Caroline; Pagani, Linda S.
Purpose: Health promotion in youth is likely to benefit from enhancing academic achievement and physical activity. The present study examines how kindergarten childhood self-regulation skills and behaviors predict involvement in both structured and unstructured physical and nonphysical extracurricular activities in the fourth grade. As a second objective this study also investigated how kindergarten childhood participation in extracurricular activities predicts classroom engagement, reflective of self-regulation, by the fourth grade. Design: Secondary analyses were conducted using prospective-longitudinal data. Setting: The Quebec Longitudinal Study of Child Development, Quebec, Canada. Subjects: Participants were randomly selected at birth from a stratified sample of 2694 born in Québec, Canada, between 1997 and 1998. Participants were included if they had complete data on teacher ratings of child self-regulation as measured by classroom engagement and parent ratings of sports participation (n = 935). Measures: Teachers reported self-regulation skills in children through a measure of classroom engagement. Parents provided reports of child participation extracurricular activities. Analysis: Ordinary least-squares regressions were conducted. Results: A higher-frequency kindergarten involvement with structured physical activities was associated with fourth-grade classroom engagement (β = .061, 95% confidence interval [CI]: .017, .104). Better kindergarten classroom engagement predicted more frequent participation in fourth-grade structured physical activities (β = .799, 95% CI: .405, 1.192) and team sports (β = .408, 95% CI: .207, .608). Conclusion: Results suggest mutual relations between physical activity and self-regulation from kindergarten to grade four. This suggests strong learning skills indicative of self-regulation and opportunities to participate in supervised physical activities or sports teams may help children develop healthy dispositions and behaviors in emerging adolescence.